Transient prenatal ruxolitinib treatment promotes neurogenesis and suppresses astrogliogenesis during embryonic mouse brain development - Abdullah, Amirah Nabilah; Fasihah Zamri, Auni; Alias, Khairunnisa; Azhar, Nur Munawwarah; Ling, King Hwa; Cheah, Pike See; Zainal Abidin, Shahidee (Neurotak Publishing, 2025)
Ruxolitinib is a Janus kinase (JAK) inhibitor that inhibits the JAK/STAT signalling pathway by targeting JAK1 and JAK2, which are crucial for regulating astrogliogenesis. This study assessed the effect of ruxolitinib (5 and 30 mg/kg/day) on developing mouse brains by administering it to pregnant mice from E7.5 to E20.5. No adverse effects were observed in the treated mice. The brains of P1.5 pups were collected, and RNA was extracted to assess markers of neurogenesis and astrogliogenesis through RT-qPCR. The results revealed a significant decrease in Gfap expression (p<0.0001) in both ruxolitinib-treated groups compared to the control, indicating a suppression of astrogliogenesis. Additionally, S100β expression (p<0.05) was significantly reduced in the 30 mg/kg ruxolitinib-treated group. In contrast, the expression of neuronal markers vGLuT1 (p<0.01) and vGLuT2 (p<0.01) increased significantly in the 30 mg/kg treated group, suggesting enhanced neuronal differentiation. Furthermore, 5 and 30 mg/kg ruxolitinib-treated groups showed a significant increase in GAT1 expression (p<0.01) compared to the control group. A marked decrease in Nestin expression was also observed in the 5 mg/kg (p<0.001) and 30 mg/kg (p<0.0001) treated groups. These findings demonstrate that transplacental administration of ruxolitinib modulates key markers involved in neuronal differentiation and gliogenesis in the developing mouse brain, suggesting its potential use in correcting imbalances in early brain development.